Meningkatkan Kualitas Mayarakat Hindu Melalui Pelatihan Pemangku dan Pemahaman Ajaran Agama Hindu di Desa Adat Yeh Embang Kangin, Kecamatan Mendoyo, Kabupaten Jembrana. - Gaduh, Acyutananda Wayan; Redi, I Wayan; Subawa, I Made Pasek; Saitya, Ida Bagus Subrahmaniam; Harsananda, Hari Harsananda (Sevanam: Jurnal Pengabdian Masyarakat, 2022)
The Hindu Theology Study Program carries out community service in the Yehembang Kangin Traditional Village, Mendoyo District, Jembrana Regency in 2021 with the theme "Training for Leadership and Understanding of Hindu Religion". The theme is adjusted to the needs of the community in the field of Kepemangkuan, the conception of tattwa, acara agama, padewasan, and Sanskrit in puja mantras to answer the challenges of religious life. This community service uses training methods by demonstrating procedures for using Genta and reciting puja mantras, as well as community education through lectures and discussions. In general, the implementation of community service received a good response from the community and was smooth. Obstacles such as the distance between the service locations and the schedule of activities that conflict with the traditional agenda can be overcome through good cooperation from all parties. During community service, it was found that the enthusiasm of the community to understand the teachings of Hinduism was very high. Especially the Pemangku who need explanations related to practices and sesana to comply with the rules of literature. The lack of literature and discussion opportunities becomes an obstacle in the public knowledge abou Hindu religious teachings. The community needs guidance related to Hindu religious teachings to prepare themselves to become a moderate society in  a pluralistic environment.